Physical Therapy Adjuvants to Promote Optimization of Walking Recovery after Stroke - Mark G. Bowden; Aaron E. Embry; Chris M. Gregory (Stroke Research and Treatment)
Stroke commonly results in substantial and persistent deficits in locomotor function. The majority of scientific inquiries have focused on singular intervention approaches, with recent attention given to task specific therapies. We propose that measurement should indicate the most critical limiting factor(s) to be addressed and that a combination of adjuvant treatments individualized to target accompanying impairment(s) will result in the greatest improvements in locomotor function. We explore training to improve walking performance by addressing a combination of: (1) walking specific motor control; (2) dynamic balance; (3) cardiorespiratory fitness and (4) muscle strength and put forward a theoretical framework to maximize the functional benefits of these strategies as physical adjuvants. The extent to which any of these impairments contribute to locomotor dysfunction is dependent on the individual and will undoubtedly change throughout the rehabilitation intervention. Thus, the ability to identify and measure the relative contributions of these elements will allow for identification of a primary intervention as well as prescription of additional adjuvant approaches. Importantly, we highlight the need for future studies as appropriate dosing of each of these elements is contingent on improving the capacity to measure each element and to titrate the contribution of each to optimal walking performance.